Multisyllabic implementation fidelity in upper elementary and professional development considerations: a pilot - Traga Philippakos, Zoi A.; Quinn, Margaret; Rocconi, Louis; Picerno, Rebekah; Davis, Adalea (Frontiers in Education, 2025)
IntroductionThis study aimed to investigate instructors' implementation fidelity of a program targeting multisyllabic decoding and encoding and its effects on upper elementary students' reading and spelling performance. Additionally, the research explored the influence of professional development (PD) and contextual factors on teachers' instructional practices.MethodsThe study involved nine female instructors from three adjacent elementary schools, including two classroom teachers who provided whole-group instruction and seven interventionists who worked with small groups. Student participants were 64 third to fifth grade learners. PD occurred prior to the study, accompanied by weekly coaching during the seven-week instructional period.ResultsResults indicated that higher fidelity of implementation for a greater number of lessons taught led to statistically significant improvements in student outcomes compared to lower fidelity for fewer lessons, which still yielded advancements in spelling and vocabulary. Furthermore, teachers exhibited significant knowledge gains from pretest to posttest, with feedback addressing factors impacting implementation fidelity.DiscussionThe study discusses implications for PD and effective program implementation.